Mature Dendritic Cells Infected with Herpes Simplex Virus Type 1 Exhibit Inhibited T-Cell Stimulatory Capacity - Kruse, Monika (American Society for Microbiology, 2000)
Mature dendritic cells (DC) are the most potent antigen-presenting cells within the entire immune system. Interference with the function of these cells therefore constitutes a very powerful mechanism for viruses to escape immune responses. Several members of the Herpesviridae family have provided examples of such escape strategies, including interference with antigen presentation and production of homologous cytokines. In this study we investigated the infection of mature DC with herpes simplex virus type 1 (HSV-1) and the way in which infection alters the phenotype and function of mature DC. Interestingly, the T-cell-stimulatory capacity of these DC was strongly impaired. Furthermore, we demonstrated that HSV-1 leads to the specific degradation of CD83, a cell surface molecule which is specifically upregulated during DC maturation. These data indicate that HSV-1 has developed yet another novel mechanism to escape immune responses.